Factors associated with safe intramuscular injection practice among nurses of a teaching hospital - Bajracharya, Rashmila (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Injection medication is one of the major responsibilities of a nurse. The principles and techniques of intramuscular (IM) injections are associated with safe nursing practice. Methods: A self-administered questionnaire for knowledge and observational checklist for procedure was used to assess the level of knowledge and practice of IM injection of nurses at Patan Hospital, Patan Academy of Health Sciences (PAHS), Nepal, during August 12 to September 07, 2018. Ethical approval was taken from Institutional Review Committee of PAHS. SPSS 16 was used for statistical analysis. Results: Out of total 78 nurses included, 5 (6.4%) had adequate knowledge, 59 (75.6%) moderate, 14 (17.9%) inadequate knowledge regarding IM injection. Similarly, out of 26 nurses observed for IM injection practices, 10 (38.5%) had good practice, 16 (61.5%) fair, and none had poor practice regarding IM injection. There was significant association of knowledge and practice of IM injection (p=0.03). Conclusions: The study shows three fourth nurses have moderately adequate level of knowledge of IM injection and more than half of them have fair practice.